PVA-Sansevieria trifasciata Fraction Films as Absorbers of Electromagnetic and Thermal Radiation on Smartphones - Rahmani, Nabiila; Syahbirin, Gustini; Maddu, Akhiruddin; Sugita, Purwantiningsih; Ilmiawati, Auliya (Makara Journal of Science, 2023)
Technological developments have prompted the production of highly advanced smartphones. However, various advanced features cause smartphones to heat up quickly and emit more electromagnetic radiation, which harms human health. Smartphone protection is needed to solve these issues. This study aims to create a film from the S. trifasciata plant based on polyvinyl alcohol (PVA) to reduce electromagnetic and thermal radiation on smartphones. S. trifasciata plants were macerated with acetone and partitioned with n-hexane, dichloromethane, ethyl acetate, and water. The films were made by mixing PVA with the four fractions. Among the four layers of film, the PVA + water and PVA + ethyl acetate fractions reduced electromagnetic radiation by 25.34% and 2.64%, respectively, and smartphone heat by 3.82 °C and 2.8 °C, respectively, the largest reductions. The results of an LC–MS/MS analysis show that the compounds thought to be contained in both fractions and play a major role in reducing electromagnetic and thermal radiation in smartphones are di-(2-ethylhexyl) phthalate, diisononyl phthalate, and two steroidal compounds, namely, stigmasterol and ergosterol peroxide.